2022
DOI: 10.3390/lubricants10050099
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Tribological Properties of the Steel/Polymer/Steel Sandwich Material LITECOR

Abstract: The article presents the results of tribological investigations into the steel/polymer/steel sandwich material LITECOR® developed by ThyssenKrupp Steel Europe for applications in the automotive industry. Friction tests were carried out by means of a strip drawing test with the use of a special tribotester mounted on a uniaxial tensile test machine. The influence of sheet deformation on the value of the coefficient of friction (COF) was considered. For this purpose, the samples were subjected to a pre-deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…)/polyethene (P.E.) core sandwiched between two steel layers [ 6 , 7 ]. The steel layers are made of HX220YD, a high-strength steel with excellent strength and stiffness while remaining lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…)/polyethene (P.E.) core sandwiched between two steel layers [ 6 , 7 ]. The steel layers are made of HX220YD, a high-strength steel with excellent strength and stiffness while remaining lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…ThyssenKrupp Steel Europe's LITECOR® composite material began to appear in several studies, including weldability by resistance spot welding [11], mechanical joining based on the mortise-tenon joint [12], and relying on three-stage joining to produce a more significant and stiffer mechanically locked joint [13]. Furthermore, studies expanded to investigate whether a commercial sandwich material can fill the role of automotive and industrial applications [14,15]. Regarding components crafted from steel-polymer sandwich composites, Hoffmann [16] demonstrated that they achieve nearly identical weight reductions compared to those composed entirely of aluminum (with only a 10% increase in weight), yet at a considerably reduced cost (at least 30% more economical).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the technology of joining, it is extremely important to master the technology of shaping new materials. The authors of the work [ 25 ] conducted a series of tests to determine the tribological properties of the LITECOR ® composite under consideration. The aim of these studies was to determine the value of the friction coefficient under various friction conditions.…”
mentioning
confidence: 99%